Pancasila as a Paradigm of Agricultural Development in Indonesia - Insi suci Mahrika; Mutiara; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Abstract - The development of modern agriculture is largely determined by the acceleration of increasing productivity, quality, and added value of production. To understand the concept of Pancasila in the agricultural revolution, namely by covering economic development in life, the agricultural revolution is one of the efforts for economic growth in Indonesia. Development will focus more on agriculture to deal with human resources who compete in agriculture. The problems that exist in agricultural development have caused some agriculture in Indonesia to be very bad, this can be seen by the weak power of farmers. Development in agriculture in Indonesia is not will be stable or not good if it is not accompanied by the norms that apply in our country. Therefore, basically Pancasila is a paradigm in development. Pancasila as a national development paradigm contains a consequence that in all aspects of national development it must be based on the values ​​of Pancasila.The development of agricultural development must be integrative through empowerment, agrarian reform, and a food sovereignty agenda within the framework of spatial planning in rural areas based on the protection of sustainable food agricultural land. This agricultural development agenda implies that the government regulates policies to protect the independence of individuals and communities that have local wisdom to rebuild food independence and sovereignty, so that national development leads to the welfare of the whole community. Keywords: agricultural development, Pancasila revolution, development paradigm